General Approach to the Magnetostatic Force and Interaction Between Cylindrically Shaped Nanoparticles - Altbir-Drullinsky, D; Escrig-Murua, J; Pereira-Abarca, A (2012)
In this paper we obtain analytical expressions for the magnetostatic interaction between cylindrical particles based on the assumption of a fixed uniform magnetization. Magnetostatic forces between the particles are established by these interactions. These general expressions allow the investigation of the magnetostatic interactions and forces between cylindrically shaped particles with different geometrical parameters like barcode-type magnetic nanostructures, multilayer nanotubes and nanowires, nanoparticles with modulated diameter, the ordering of nanoparticles on fluids, and others. © 2012 American Institute of Physics.